Autologous albumin enhances the humoral immune response to capsular polysaccharide covalently coattached to bacteria‐sized latex beads. Issue 5 (27th February 2014) - Colino, Jesus; Duke, Leah; Snapper, Clifford M.
<x xml:space="preserve">Abstract</x> Abundant autologous proteins, like serum albumin, should be immunologically inert. However, individuals with no apparent predisposition to autoimmune disease can develop immune responses to autologous therapeutic proteins. Protein aggregation is a potential major trigger of these responses. Adsorption of proteins to particles provides macromolecular size and may generate structural changes in the protein, resembling aggregation. Using aldehyde/sulfate latex beads coated with murine serum albumin (MSA), we found that BALB/c mice mounted MSA‐specific IgG responses that were dependent on CD4+ T cells. IgGs were specific for MSA adsorbed to solid surfaces and noncross‐reactive with human, bovine, or pig albumins. T cells induced in response to MSA augmented the primary and induced boosted secondary IgG and IgM responses specific for the T cell‐independent antigen, capsular polysaccharide of Streptococcus pneumoniae type 14 (PPS14), when the latter was attached to the same bead. Similar to the anti‐MSA IgG response, the boosted PPS14‐specific IgG secondary response was CD4+ T‐cell dependent, displayed a typical carrier effect, and was enhanced by, but did not require, Toll‐like receptor stimulation. These results provide a potential mechanism for the induction of responses to autoantigens unable to induce specific T‐cell responses, and provide new insights into polysaccharide‐specific immunity.